ANALISIS DAMPAK PELATIHAN AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN DAN FAKTOR-FAKTOR PENENTU KEBERHASILAN - Kurniawan, Kurniawan; Rifvany, Nia; Rahmawati, Risa Lailatul (Gapenas Publisher, 2025)
This study aims to analyze the impact of accounting training on the quality of financial reports and identify the determinants of successful adoption of accounting practices in Micro, Small, and Medium Enterprises (MSMEs) and Village-Owned Enterprises (BUMDesa) in Greater Mojokerto. This study uses a mixed methods approach (mixed methods) with primary data collected through an online questionnaire from 21 respondents. Data analysis was conducted using quantitative descriptive and qualitative content analysis. The results showed that accounting training had a very positive impact on increasing knowledge (average score 4.44/5) and skills (4.39/5), which directly improved the quality of financial reports and their use for business decision-making (4.50/5). The most dominant determinant of success from the internal side was high personal motivation (4.81/5), while from the quality of training, a simple and practical approach (4.57/5) and the need for ongoing mentoring (4.52/5) were key. This study recommends that training providers focus on practical materials and provide post-training mentoring programs to ensure sustainable implementation